Diversification of mineralocorticoid receptor genes in a subterranean rodent, the naked mole-rat. (11th May 2021) - Oka, Kaori; Bono, Hidemasa; Kuroiwa, Asato; Fujioka, Shusuke; Shimizu, Atsushi; Katsu, Yoshinao; Miura, Kyoko
Abstract : Naked mole-rats ( Heterocephalus glaber ) inhabit subterranean burrows in savannas and are, thus, unable to access free water. To identify their mechanism of osmoregulation in xeric environments, we molecularly cloned and analyzed the nuclear receptor subfamily 3 group C member 2 ( NR3C2 ) gene encoding the mineralocorticoid receptor (MR), required for hormone-dependent regulation of genes contributing to body fluid homeostasis. Most vertebrates harbor a single MR homolog. In contrast, we discovered that MR is duplicated in naked mole-rats. The amino acid sequence of naked mole-rat MR1 is 90% identical to its mouse ortholog, and MR1 is abundantly expressed in the kidney and the nervous system. MR2 encodes a truncated protein lacking DNA- and ligand-binding domains of MR1 and is expressed in diverse tissues. Although MR2 did not directly transactivate gene expression, it increased corticosteroid-dependent transcriptional activity of MR1. Our results suggest that MR2 might function as a novel regulator of MR1 activity to fine-tune MR signaling in naked mole-rats.